Changes in motor preparation affect the sensory consequences of voice production in voice hearers. (September 2020) - Pinheiro, Ana P.; Schwartze, Michael; Amorim, Maria; Coentre, Ricardo; Levy, Pedro; Kotz, Sonja A.
Abstract: Background: Auditory verbal hallucinations (AVH) are a cardinal symptom of psychosis but are also present in 6–13% of the general population. Alterations in sensory feedback processing are a likely cause of AVH, indicative of changes in the forward model. However, it is unknown whether such alterations are related to anomalies in forming an efference copy during action preparation, selective for voices, and similar along the psychosis continuum. By directly comparing psychotic and nonclinical voice hearers (NCVH), the current study specifies whether and how AVH proneness modulates both the efference copy (Readiness Potential) and sensory feedback processing for voices and tones (N1, P2) with event-related brain potentials (ERPs). Methods: Controls with low AVH proneness (n = 15), NCVH (n = 16) and first-episode psychotic patients with AVH (n = 16) engaged in a button-press task with two types of stimuli: self-initiated and externally generated self-voices or tones during EEG recordings. Results: Groups differed in sensory feedback processing of expected and actual feedback: NCVH displayed an atypically enhanced N1 to self-initiated voices, while N1 suppression was reduced in psychotic patients. P2 suppression for voices and tones was strongest in NCVH, but absent for voices in patients. Motor activity preceding the button press was reduced in NCVH and patients, specifically for sensory feedback to self-voice in NCVH. Conclusions: These findings suggest that selective changes in sensory feedback to voice are core to AVH. These changes already show in preparatory motor activity, potentially reflecting changes in forming an efference copy. The results provide partial support for continuum models of psychosis. Highlights: We assessed how hallucination proneness modulates the efference copy and sensory feedback processing. N1 was enhanced to self-initiated voices in nonclinical voice hearers. N1 suppression was reduced in psychotic voice hearers. The Readiness Potential was reduced before voice elicitation in nonclinical voice hearers. Selective changes in sensory feedback to voice are core to auditory verbal hallucinations.